2014
DOI: 10.3329/bjvm.v11i1.17732
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and immunological characterization of anthrax vaccine in cattle

Abstract: Anthrax is a zoonotic disease caused by the bacterium Bacillus anthracis that normally affects animals, especially ruminants (such as cattle, goats, sheep, and horses) and humans. This study was planned to characterize the morphology of anthrax vaccine bacteria by using Gram’s stain, polychrome methylene blue stain, culture on nutrient agar and nutrient broth media and to determine the immunological status of this vaccine by indirect ELISA and slide agglutination test in cattle. Antibiotic sensitivity test of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 2 publications
(1 reference statement)
2
14
1
Order By: Relevance
“…Vaccination response as obtained in this study differed from the finding of Dipti et al (2013) and Roy et al (2013) although they used same vaccine that we used in our study, who could detect early immune response in cattle at day 30 of immunization; whereas, in the present study we revealed early response at day 7 of post-vaccination. In addition, Dipti et al (2013) described a steady increase in antibody level upto 90days.…”
Section: Resultscontrasting
confidence: 72%
See 3 more Smart Citations
“…Vaccination response as obtained in this study differed from the finding of Dipti et al (2013) and Roy et al (2013) although they used same vaccine that we used in our study, who could detect early immune response in cattle at day 30 of immunization; whereas, in the present study we revealed early response at day 7 of post-vaccination. In addition, Dipti et al (2013) described a steady increase in antibody level upto 90days.…”
Section: Resultscontrasting
confidence: 72%
“…In addition, Dipti et al (2013) described a steady increase in antibody level upto 90days. In contrast, we found the antibody level was fluctuating over the study period (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Then it was incubated at 37ºC for over night. No growth of bacteria around the particular disc was considered as sensitive to that antibiotic, growth of bacteria around the disc was considered as resistance to that particular antibiotic and partial growth was considered as partially resistant to that particular antibiotic (Dipti, 2013).…”
Section: Antibiotics Sensitivity Testmentioning
confidence: 99%